2023
DOI: 10.1007/s00125-022-05861-9
|View full text |Cite
|
Sign up to set email alerts
|

Counter-regulatory responses to postprandial hypoglycaemia in patients with post-bariatric hypoglycaemia vs surgical and non-surgical control individuals

Abstract: Aims/hypothesis Post-bariatric hypoglycaemia is an increasingly recognised complication of bariatric surgery, manifesting particularly after Roux-en-Y gastric bypass. While hyperinsulinaemia is an established pathophysiological feature, the role of counter-regulation remains unclear. We aimed to assess counter-regulatory hormones and glucose fluxes during insulin-induced postprandial hypoglycaemia in patients with post-bariatric hypoglycaemia after Roux-en-Y gastric bypass vs surgical and non-sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…An imbalance in the counter-regulatory response mediated by glucagon has also been suggested; specifically, lower early peak levels have been observed after MMTT in patients with hypoglycemia, which were unable to counter-regulate the over-elevated levels of insulin [ 12 , 13 ]. Even though this mitigated glucagon response has been consistently reported in several studies, some authors have not observed a significant difference in levels of patients with no PBH after RYGB [ 15 ], suggesting that this analytical finding may be inherent to altered post-bariatric surgery physiology, in the setting of sustained weight loss and lower nadir glucose levels, and not a true cause of PBH. Interestingly, in the aforementioned study, the authors found that levels of pancreatic polypeptide (PP) were significantly decreased in patients with PBH, in comparison to the control group.…”
Section: Discussionmentioning
confidence: 80%
“…An imbalance in the counter-regulatory response mediated by glucagon has also been suggested; specifically, lower early peak levels have been observed after MMTT in patients with hypoglycemia, which were unable to counter-regulate the over-elevated levels of insulin [ 12 , 13 ]. Even though this mitigated glucagon response has been consistently reported in several studies, some authors have not observed a significant difference in levels of patients with no PBH after RYGB [ 15 ], suggesting that this analytical finding may be inherent to altered post-bariatric surgery physiology, in the setting of sustained weight loss and lower nadir glucose levels, and not a true cause of PBH. Interestingly, in the aforementioned study, the authors found that levels of pancreatic polypeptide (PP) were significantly decreased in patients with PBH, in comparison to the control group.…”
Section: Discussionmentioning
confidence: 80%
“…Further characteristics of the population (e.g. body composition) are available in Tripyla et al 13 Of the 32 total participants, two (both in the GB non-PBH group)…”
Section: Resultsmentioning
confidence: 99%
“…This introduces a confounding effect in evaluating Gluclas, as the contribution of Gluclas to the success of the clamps cannot be fully disentangled from the contribution of the clinical team. On the other hand, this choice enabled testing Gluclas in a clinical trial designed for other purposes, 13 without exposing the patients to the risks associated with a trial exclusively dedicated to the evaluation of Glucas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations